Perinatal Practices & Traditions Among Asian Indian Women. Issue 2 (March 2016) - Goyal, Deepika
Abstract : Abstract: As the population in the United States grows more diverse, nurses caring for childbearing women must be aware of the many cultural traditions and customs unique to their patients. This knowledge and insight supports women and their families with the appropriate care, information, and resources. A supportive relationship builds trust, offers guidance, and allows for the new family to integrate information from nurses and other healthcare providers with the practice of certain perinatal cultural traditions. The Asian Indian culture is rich in tradition, specifically during the perinatal period. To support the cultural beliefs and practices of Asian Indian women during this time, nurses need to be aware of and consider multiple factors. Many women are navigating the new role of motherhood while making sense of and incorporating important cultural rituals. The purpose of this article is to provide an overview of perinatal cultural practices and traditions specific to the Asian Indian culture that perinatal nurses may observe in the clinical setting. Cultural traditions and practices specific to the pregnancy and postpartum period are described together with symbolism and implications for nursing practice. It is important to note that information regarding perinatal customs is provided in an effort to promote culturally sensitive nursing care and may not pertain to all Asian Indian women living in the United States. Abstract : Asian Indian women living in the United States have many cultural practices and traditions related to pregnancy, birth, and postpartum. An overview is provided to help perinatal nurses give quality care to this unique and growing population.